Characteristics of the last five surges of Lowell Glacier, Yukon, Canada, since 1948. Issue 219 (2014) - Bevington, Alexandre; Copland, Luke
Abstract: Field observations, aerial photographs and satellite images are used to reconstruct the past surges of Lowell Glacier, Yukon, Canada, since 1948 based on the timing of terminus advances. A total of five surges occurred over this time, each with a duration of 1–2 years. The time between successive surges ranged from 12 to 20 years, and appears to have been shortening over time. The relatively short advance and quiescent phases of Lowell Glacier, together with rapid increases in velocity during surges, suggest that the surging is controlled by a hydrological switch. The 2009–10 surge saw ablation area velocities increase by up to two orders of magnitude from quiescent velocities, and the terminus increase in area by 5.1 km 2 and in length by up to 2.85 km. This change in area was the smallest since 1948, and follows the trend of decreasing surge extents over time. This decrease is likely driven by a strongly negative surface mass balance of Lowell Glacier since at least the 1970s, and means that the current town site of Haines Junction is very unlikely to be flooded by damming caused by any future advances of the glacier under the current climate regime.